Clinical features and progression of Parkinson's disease with LRRK2 variants: A prospective study - Tingwei Song; Xiaoxia Zhou; Chunyu Wang; Heng Wu; Xinxiang Yan; Jifeng Guo; Beisha Tang; Lifang Lei; Qian Xu; Parkinson's Disease & Movement Disorders Multicenter Database and Collaborative Network in China (PD‐MDCNC) (Annals of Clinical and Translational Neurology)
Abstract Objective We established a prospective cohort study to investigate the differences in motor and non‐motor symptoms between idiopathic Parkinson's disease (IPD) and Parkinson's disease in carriers of leucine‐rich repeat kinase 2 (LRRK2) gene risk variants (LRRK2‐PD). Methods The study included 1407 individuals with IPD and 649 individuals with LRRK2‐PD (comprising 304 with LRRK2‐G2385R, 220 with LRRK2‐R1628P, and 105 with LRRK2‐A419V). Differences in symptoms between LRRK2‐PD and IPD were analyzed using LCMM modeling and Cox regression analysis. Results The LRRK2‐G2385R variant showed slower progression in tremor symptoms and excessive daytime sleepiness compared with IPD. In contrast, symptoms associated with LRRK2‐R1628P and LRRK2‐A419V were more similar to those of IPD. Survival analysis revealed that LRRK2‐PD does not affect life expectancy compared with IPD. Interpretation Our extended longitudinal follow‐up of LRRK2‐PD in the Chinese population provided valuable insights, further confirming the clinical characteristics of the three LRRK2 variants.